Pelatihan Pengembangan Konten Berbasis Artificial Intelligence dalam Mendukung Pariwisata Lombok - Hamdi, Saipul; Chaniago, Dwi Setiawan; Rani, Anisa Puspa; Haromain, Nurul (Insan Kreasi Media, 2025)
The digitalization era has brought significant changes to tourism marketing in Indonesia, yet many tourist villages have not fully optimized the use of digital technology to create attractive promotional content. This community service program was designed to strengthen the digital capacity of Lebah Sempage Tourism Village in West Lombok Regency, which has great tourism potential but faces challenges in content creation and dissemination. The main objective was to introduce the community to AI-based tools that are free, practical, and accessible through smartphones, enabling them to produce engaging promotional materials. The program applied a Community-Based Learning approach combined with Transfer of Knowledge methodology. A one-day seminar was conducted with 28 participants, consisting of BUMDesa managers, members of the Tourism Awareness Group, local entrepreneurs, and youth organizations. The training provided step-by-step modules on how to utilize AI applications for generating promotional images, writing social media captions, and developing tourism content. The results showed positive impacts, including increased awareness of digital technology, the formation of informal peer discussion groups, and the rise of local digital champions. These outcomes highlight that digital transformation at the grassroots level does not necessarily require sophisticated infrastructure but rather effective strategies for transferring practical knowledge. In conclusion, this program contributed to sustainable community empowerment by enhancing digital marketing skills to support tourism development.